The Contribution of the Dr. Gustavo Aldereguía Lima Hospital to Medical Education in Cienfuegos, 1979-2016 - Alfredo Darío Espinosa Brito (Medisur)
This paper presents a historical review of the contribution of the Dr. Gustavo Alderguía Lima Hospital to the emergence and development of higher medical education in Cienfuegos, emphasizing on the early stages. It highlights the fact that, true to the provincial tradition, everything was organized, implemented and developed with our own professionals. It includes some events that demonstrate the role played by this institution, its faculty, workers in general, and undergraduate and graduate students in achieving better health and education in the province, as well as the integration with other institutions. A group of difficulties and challenges in the field of teaching faced by the hospital for almost four decades is also discussed. It is argued that the university hospital of the future in Cienfuegos must be based on the general policies of our health system, but adapting them to the local context to be consistent with Marti's dream "with all and for the good of all", bearing in mind that we have to fulfill the mandate that the hospital must be “a symbol of the health, life, and happiness of the people of Cienfuegos” and that “it is impossible to close the doors”.